Beliefs and attitudes from river plate speakers towards the chilean variety - Gutiérrez Böhmer, Sofía; Borzi, Claudia (Lenguas Modernas, 2023)
This work is part of the “Project for the study of beliefs and attitudes towards varieties of Spanish in the 21st century” (PRECAVES XXI), focusing this time on the evaluation of speakers of Buenos Aires towards the Chilean variety. It follows the same methodology as a previous study carried out on Castilian variety to advance in the comparison of different varieties of Spanish. Only one type of identification is considered, the correct one, and two significance criteria: rating scale for the variety and distance between values. It is noted that the speakers of Buenos Aires clearly identify the Chilean variety and that they assign it a valuation located preferably within the slightly positive zone. The expansion of the sample of interviewees with secondary education allows some sociolinguistic conclusions.